Managing patients using telerheumatology: Lessons from a pandemic. Issue 1 (March 2021) - Bateman, James; Cleaton, Natasha
Abstract: The coronavirus disease 2019 (COVID-19) pandemic has presented unique challenges to rheumatology provision. Measures to control the pandemic have limited face-to-face contact with rheumatology healthcare professionals. One innovation has been the widespread adoption of telerheumatology to assist in the care of patients with rheumatic and musculoskeletal diseases, building on an existing evidence base in rheumatology. Widespread adoption has only occurred following the COVID-19 pandemic. We discuss the evidence supporting telerheumatology adoption prior to the pandemic, and outline several innovative approaches used to assist in the care of rheumatology patients that have been introduced. Alongside the advantages of these interventions, we discuss the limitations and regulatory challenges. Advances must be balanced, considering wider issues of equity of access, implementation, adoption, and sustainability of telerheumatology post-pandemic. We propose it is not 'if', but 'how' rheumatologists embrace newer telerheumatology technology, outlining practice points and future research agenda.